SEG Technical Program Expanded Abstracts 2016 2016
DOI: 10.1190/segam2016-13845123.1
|View full text |Cite
|
Sign up to set email alerts
|

Imaging near-surface heterogeneities by natural migration of surface waves

Abstract: SUMMARYWe demonstrate that near-surface heterogeneities can be imaged by natural migration of backscattered surface waves in common shot gathers. No velocity model is required because the data are migrated onto surface points with the virtual Green's functions computed from the shot gathers. Migrating shot gathers recorded by 2D and 3D land surveys validates the effectiveness of detecting near-surface heterogeneities by natural migration. The implication is that more accurate hazard maps can be created by migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…Figure 8a next to the conjectured fault is consistent with the downthrown-side of an interpreted normal fault. The LVZ is also consistent with the reflectivities of the migration image (Liu et al, 2016(Liu et al, , 2017 indicated by the blue zone next to the dashed fault in Figure 8b. This LVZ next to the fault is accompanied by a delay in the surface-wave arrivals shown in the common offset gathers (COG) in Figure 8c.…”
Section: Qademah Fault Seismic Datasupporting
confidence: 81%
“…Figure 8a next to the conjectured fault is consistent with the downthrown-side of an interpreted normal fault. The LVZ is also consistent with the reflectivities of the migration image (Liu et al, 2016(Liu et al, , 2017 indicated by the blue zone next to the dashed fault in Figure 8b. This LVZ next to the fault is accompanied by a delay in the surface-wave arrivals shown in the common offset gathers (COG) in Figure 8c.…”
Section: Qademah Fault Seismic Datasupporting
confidence: 81%
“…The blue low-velocity zone (LVZ) in Figure 8a next to the conjectured fault is consistent with the downthrown-side of an interpreted normal fault. The LVZ is also consistent with the reflectivities of the migration image (Liu et al, 2016(Liu et al, , 2017 indicated by the blue zone next to the dashed fault in Figure 8b. This LVZ next to the fault is accompanied by a delay in the surface-wave arrivals shown in the common offset gathers (COG) in Figure 8c.…”
Section: Numerical Examples Modified Foothills Modelsupporting
confidence: 81%
“…In recent years, shallow seismic exploration has attracted increasing attention (Liu, et al ., 2016; Feigenbaum, et al ., 2017; Oktariena and Triyoso, 2018; Wo, et al ., 2018; Zheng, 2018; Gallais, et al ., 2019; Mahvelati, et al ., 2019; Shakuro, 2019; Song, et al ., 2019; Wang, 2019; Zhenbo, et al ., 2019; Sun, et al ., 2020). Near‐surface structures are complex, and the seismic wave fields are rich and variable, which cause difficulties for seismic migration (Almuhaidib and Toksöz, 2014; Krohn and Murray, 2016; Dehghannejad, et al ., 2017; Alam, 2019).…”
Section: Introductionmentioning
confidence: 99%